SELF-ASSESSMENT IN THE CREDIT-MODULAR SYSTEM AS A FACTOR IN ENHANCING STUDENT ENGAGEMENT (Web of Teachers: Inderscience Research, 2025)
This article examines the role of self-assessment in enhancing student engagement within the credit-modular system of higher education. It explores how self-assessment strategies support students’ active learning, promote metacognitive awareness, and contribute to the development of academic independence. Empirical findings and pedagogical insights from contemporary studies are reviewed to evaluate the effectiveness of integrating self-assessment in modular course structures. The article also discusses potential challenges and practical recommendations for instructors.